Protein type and caloric density of protein supplements modulate postprandial amino acid profile through changes in gastrointestinal behaviour: A randomized trial. Issue 1 (February 2016) - Luiking, Yvette C.; Abrahamse, Evan; Ludwig, Thomas; Boirie, Yves; Verlaan, Sjors
Summary: Background & aims: The requirement of leucine and essential amino acids (EAA) to stimulate muscle protein synthesis increases with age. To target muscle anabolism it is suggested that higher postprandial blood levels of leucine and EAA are needed in older people. The aim was to evaluate the impact of oral nutritional supplements with distinct protein source and energy density, resembling mixed meals, on serum amino acid profiles and on gastrointestinal behaviour. Methods: Four iso-nitrogenous protein (21 g) supplements were studied containing leucine-enriched whey protein with 150/320 kcal (W150/W320) or casein protein with 150/320 kcal (C150/C320); all products contained carbohydrates (10 or 32 g) and fat (3 or 12 g). Postprandial serum AA profiles were evaluated in twelve healthy, older subjects who participated in a randomized, controlled, single blind, cross-over study. Gastrointestinal behaviour was studied in vitro by looking at gastric coagulation and cumulative intestinal protein digestion over time. Results: The peak serum leucine concentration was twofold higher for W150 vs. C150 (521 ± 15 vs. 260 ± 15 μmol/L, p < 0.001), higher for W320 vs. C320 (406 ± 15 vs. 228 ± 15 μmol/L, p < 0.001), and higher for low-caloric vs. high-caloric products (p < 0.001 for pooled analyses; p < 0.001 for interaction protein source*caloric density). Similar effects were observed for the peak concentrations of EAA and total AA (TAA). In vitro gastric coagulation was observed only for the casein protein supplements. Intestinal digestion for 90 min resulted in higher levels of free TAA, EAA, and leucine for W150 vs. C150, for W150 vs. W320, and for C150 vs. C320 (p < 0.0125). Conclusions: A low caloric leucine-enriched whey protein nutritional supplement provides a higher rise in serum levels of TAA, EAA and leucine compared to casein protein or high caloric products in healthy, elderly subjects. These differences appear to be mediated in part by the gastrointestinal behaviour of these products. Clinical trial registration: ClinicalTrials.gov: NCT02013466 .